English grammar an introduction - Collins, Peter 1950-; Hollo, Carmella (Palgrave Macmillan, 2010)
"This new edition of a successful text has been thoroughly revised to make it even more accessible to those without any prior grammatical knowledge. There is greater discussion and exemplification of key terms, while essential topics are now fully introduced at the outset. There are also new sections, more diagrams and shaded boxes"--Provided by publisher.